Cinnamyl alcohol modified chitosan oligosaccharide for enhancing antimicrobial activity - Yue, Lin; Sun, Dan; Mahmood Khan, Imran; Liu, Xiaoli; Jiang, Qixing; Xia, Wenshui (Food chemistry, 2020)
•COS-O-Cin1-3 were synthesized via substitution and deprotection reaction.•COS-O-Cin1-3 were identified by FT-IR, 1H NMR, UV–vis, etc.•COS-O-Cin1-3 exhibited a better antibacterial properties compared to COS.•COS-O-Cin1-3 exhibited better stability and solubility than Cin in distilled water. The present study aims at synthesizing and in vitro antibacterial activity evaluation of chitosan oligosaccharide (COS) modified by Cinnamyl alcohol (Cin) onto the OH position of COS. Three different degrees of substitution (DS) COS-O-Cin1-3 were synthesized by changing different molar ratios of COS to Cin. UV–visible spectroscopy (UV–vis), Fourier transform infrared (FT-IR), 1H nuclear magnetic resonance (1H NMR), thermogravimetric analysis (TGA), X-ray diffraction (XRD) and elemental analysis were conducted to characterize the successful synthesis of COS-O-Cin1-3. The results showed that they exhibited higher thermal stability, weaker crystallinity and better antibacterial properties than that of COS. These results aided in obtaining the important supports for exploring new functional antibacterial agents, which expand the scope of COS’s application in the food industry.